Epac-Rap signaling reduces oxidative stress in the tubular epithelium - Stokman, Geurt; Qin, Yu; Booij, Tijmen H; Ramaiahgari, Sreenivasa; Lacombe, Marie; Dolman, M Emmy M; van Dorenmalen, Kim M A; Teske, Gwendoline J D; Florquin, Sandrine; Schwede, Frank; van de Water, Bob; Kok, Robbert J; et al. (Journal of the American Society of Nephrology, 2014)
Activation of Rap1 by exchange protein activated by cAMP (Epac) promotes cell adhesion and actin cytoskeletal polarization. Pharmacologic activation of Epac-Rap signaling by the Epac-selective cAMP analog 8-pCPT-2'-O-Me-cAMP during ischemia-reperfusion (IR) injury reduces renal failure and application of 8-pCPT-2'-O-Me-cAMP promotes renal cell survival during exposure to the nephrotoxicant cisplatin. Here, we found that activation of Epac by 8-pCPT-2'-O-Me-cAMP reduced production of reactive oxygen species during reoxygenation after hypoxia by decreasing mitochondrial superoxide production. Epac activation prevented disruption of tubular morphology during diethyl maleate-induced oxidative stress in an organotypic three-dimensional culture assay. In vivo renal targeting of 8-pCPT-2'-O-Me-cAMP to proximal tubules using a kidney-selective drug carrier approach resulted in prolonged activation of Rap1 compared with nonconjugated 8-pCPT-2'-O-Me-cAMP. Activation of Epac reduced antioxidant signaling during IR injury and prevented tubular epithelial injury, apoptosis, and renal failure. Our data suggest that Epac1 decreases reactive oxygen species production by preventing mitochondrial superoxide formation during IR injury, thus limiting the degree of oxidative stress. These findings indicate a new role for activation of Epac as a therapeutic application in renal injury associated with oxidative stress.